Impaired Online and Enhanced Offline Motor Sequence Learning in Individuals with Parkinson's Disease - Van Roy, Anke; Dan, Xiaojuan; Micca, Letizia; Gilat, Moran; Chan, Piu; Doyon, Julien; Albouy, Genevieve; King, Bradley R (The Journal of neuroscience, 2025)
Whereas memory consolidation research has traditionally focused on longer temporal windows (i.e., hours to days) following an initial learning episode, recent research has also examined the functional significance of the shorter rest epochs interspersed with blocks of task practice (i.e., "micro-offline" intervals on the timescale of seconds to minutes). In the motor sequence learning (MSL) domain, evidence from young, healthy individuals suggests that micro-offline epochs afford a rapid consolidation process that is supported by the hippocampus. Consistent with these findings, amnesic patients with hippocampal damage were recently found to exhibit degraded micro-offline performance improvements. These offline losses were compensated for by larger performance gains during online practice. Given the known role of the striatum in online MSL, we hypothesized that individuals with dysfunction of the striatal system would exhibit impaired online, yet enhanced micro-offline, learning (i.e., a pattern of results opposite to that observed in patients with hippocampal damage). We tested this hypothesis using Parkinson's disease (PD) as a model of striatal dysfunction. Forty-two drug-naive individuals with a clinical diagnosis of unilateral PD and 30 healthy control subjects completed a MSL paradigm (participants included both men and women). Relative to age-similar controls, individuals with PD exhibited deficits during online task practice that were paralleled by greater improvements over micro-offline intervals. Results could not be explained by disease-related deficits in movement execution. These data suggest that striatal dysfunction disrupts online learning, yet total learning remains unchanged because of greater micro-offline performance improvements that potentially reflect hippocampal-mediated compensatory processes.